Răspuns :
Notăm:
x+2 = a, x- 3 = b și expresia devine:
(a/b - b/a -25/ab) :5/a = [(a² -b² -25)/ab] ·a/5 = (a² -b² -25)/5b (1)
Dar, a - b = x+2 - x + 3 ⇒ a- b=5 ⇒ a = 5+b ⇒ a² =25+10b+b² (2)
Din (1), (2) ⇒ expresia devine:
(25+10b+ b² - b² - 25)/5b = 10b/5b = 2
x+2 = a, x- 3 = b și expresia devine:
(a/b - b/a -25/ab) :5/a = [(a² -b² -25)/ab] ·a/5 = (a² -b² -25)/5b (1)
Dar, a - b = x+2 - x + 3 ⇒ a- b=5 ⇒ a = 5+b ⇒ a² =25+10b+b² (2)
Din (1), (2) ⇒ expresia devine:
(25+10b+ b² - b² - 25)/5b = 10b/5b = 2